2016
DOI: 10.5397/cise.2016.19.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Stabilization for Displaced Lateral Clavicular Fractures: Can It Restore Anatomy?

Abstract: Background: The purpose of our study was to evaluate the accuracy of reduction based on postoperative computed tomography (CT) images after arthroscopic stabilization using tightrope system for unstable distal clavicle fracture. Methods: Twelve patients with distal clavicle fracture combined with coracoclavicular (CC) ligament injury (type II, V) who received arthroscopically assisted fixation using a flip button device were evaluated for accuracy of reduction using 3-dimensional postoperative CT scan by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…They concluded that indirect reduction and arthroscopic subacromial approach with flip button fixation of unstable lateral clavicle fractures demonstrated favorable clinical results despite unavoidable posterior angulation of the distal clavicle and shortening the total length of clavicle. However, these results reported by Khan et al 5) need to be treated cautiously. First, 2 patients (16.7%) underwent revision surgery due to incomplete reduction.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…They concluded that indirect reduction and arthroscopic subacromial approach with flip button fixation of unstable lateral clavicle fractures demonstrated favorable clinical results despite unavoidable posterior angulation of the distal clavicle and shortening the total length of clavicle. However, these results reported by Khan et al 5) need to be treated cautiously. First, 2 patients (16.7%) underwent revision surgery due to incomplete reduction.…”
mentioning
confidence: 49%
“…[2][3][4] In this issue, the study "Arthroscopic stabilization for displaced lateral clavicular fractures: Can it restore anatomy?" by Khan et al 5) presented a series of 12 patients who were treated with arthroscopically assisted CC stabilization using a flip button device. Ten patients had complete restoration of the CC distance and bony union without loss of reduction at the serial plain radiographs.…”
mentioning
confidence: 99%